Respuesta :
If you would like to find the equivalent expression to 486 – 9 + 6 + 33 × 2, you can do this using the following steps:
486 – 9 + 6 + 33 × 2 = (486 – 9 + 6) + (33 × 2) = 483 + 66 = 549
The correct result would be D. (486 – 9 + 6) + (33 × 2).
486 – 9 + 6 + 33 × 2 = (486 – 9 + 6) + (33 × 2) = 483 + 66 = 549
The correct result would be D. (486 – 9 + 6) + (33 × 2).
Expression equivalent to 486 – 9 + 6 + 33 × 2 will be :
486 – 9 + 6 + 33 × 2 = (486 – 9 + 6) + (33 × 2)
Proof :
Solving both sides by DMAS rule,
486-9+6+66 = 483+66
477+6+66=549
549=549
486 – 9 + 6 + 33 × 2 = (486 – 9 + 6) + (33 × 2)
Proof :
Solving both sides by DMAS rule,
486-9+6+66 = 483+66
477+6+66=549
549=549